2020
DOI: 10.21203/rs.3.rs-47146/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Family planning uptake in Kagera and Mara regions in Tanzania: a cross-sectional community survey

Abstract: BackgroundIn Tanzania, 27.1% of all women of reproductive age are currently using modern contraception, and 16.8% have an unmet need for family planning. We therefore examined factors associated with family planning uptake after giving birth in two regions of Tanzania.MethodsSub-analysis of a cross-sectional household survey conducted in April 2016 in Mara and Kagera regions in Tanzania. A total of 1184 women aged 15-49 years, who had given birth less than two years prior to the survey were included. Logistic … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
3
1
0
Order By: Relevance
“…Lastly, the ndings also indicate that discussing FP matters with sexual partners increased the utilization by more than six-times compared to those who did not. The ndings are in line with [41] who found that discussing FP with sexual partner increased the utilization. Similar ndings were reported from a study conducted in Ethiopia [42].…”
Section: Discussionsupporting
confidence: 88%
“…Lastly, the ndings also indicate that discussing FP matters with sexual partners increased the utilization by more than six-times compared to those who did not. The ndings are in line with [41] who found that discussing FP with sexual partner increased the utilization. Similar ndings were reported from a study conducted in Ethiopia [42].…”
Section: Discussionsupporting
confidence: 88%
“…As for the delay in the first birth control, frequent communication between spouses, which presumably includes birth control questions, affects birth control in the past (increasing the probability of use by 40 percentage points), but not during the survey. Similar to findings in Link [ 44 ], Sharan and Valente [ 45 ], and Massenga et al [ 46 ], better communication between the husband and wife increases contraception use, perhaps because they often pondered it jointly.A woman having more education is associated with a greater use of contraception, whether in the past (22 percentage points higher probability of use, relative to women with no education) or during the survey (15 percentage points higher). The literature has long shown that women’s schooling favors more effective and intensive use of contraceptive methods [ 27 , 46 49 ].…”
Section: Results Discussionsupporting
confidence: 77%
“…Similar to findings in Link [ 44 ], Sharan and Valente [ 45 ], and Massenga et al [ 46 ], better communication between the husband and wife increases contraception use, perhaps because they often pondered it jointly.A woman having more education is associated with a greater use of contraception, whether in the past (22 percentage points higher probability of use, relative to women with no education) or during the survey (15 percentage points higher). The literature has long shown that women’s schooling favors more effective and intensive use of contraceptive methods [ 27 , 46 49 ]. As before, male education does not influence contraception, in contrast to Cochrane and Guilkey’s [ 50 ] findings for Tunisia in 1988.…”
Section: Results Discussionsupporting
confidence: 77%
“…The number of children desired is slightly negatively associated with the probability of current contraceptive use (-4 percent probability per additional child), as in Bollen et al [ 57 ] for 1988 Tunisia, and it does not signi cantly affect past use. The latter may be because fertility goals may change over time.…”
Section: Contraceptive Usementioning
confidence: 70%